Advanced, contemporary control : Proceedings of KKA 2020--The 20th Polish Control Conference, Łódź, Poland, 2020 /: Proceedings of KKA 2020--The 20th Polish Control Conference, Łódź, Poland, 2020. (2020) - Unknown
No abstract available